International Health Tourism: A Strategic Comparison of Türkiye and Germany - BULUT, CANAN (İstanbul Gelişim Üniversitesi Yayınları, 2025)
Aim: This study aims to conduct an in-depth analysis of the competitive dynamics of health tourism in Türkiye and Germany by utilizing current data. The primary goal is to identify the strategic advantages and challenges each country faces within the health tourism sector. Method: The research employs a comparative approach, analyzing quantitative data related to healthcare costs, treatment options, service quality, patient safety, and satisfaction levels in both Türkiye and Germany. Secondary data sources, such as industry reports and healthcare statistics, form the foundation of this analysis. Results: The study reveals that Türkiye emerges as an attractive destination due to its cost advantages, with healthcare services being 50-70% lower compared to Germany, alongside a wide variety of treatment options. Its geographical position and accessibility further enhance its appeal to health tourists. In contrast, Germany is recognized for its high-quality healthcare services, accredited hospitals, and specialized professionals, ensuring patient safety and treatment excellence. Both countries report high patient satisfaction rates; however, Türkiye faces certain service-related challenges that can impact the patient experience negatively. Conclusion: This research presents a clear overview of the strategic positions and potential growth areas of both Türkiye and Germany in health tourism. It serves as a valuable reference for future development strategies aimed at strengthening their competitive standings in the international health tourism market.
Uluslararası Sağlık Turizmi: Türkiye ve Almanya'nın Stratejik Karşılaştırması
Keywords: Health Tourism; Patient Satisfaction; Cost; Health Policy